PRAKSIS KONSERVASI ALAM PADA ETNIS LAMAHOLOT: PARADIGMA ECO-RELIGI - Kenoba, Marianus Ola; Bala, Alexander (Universitas Negeri Malang, 2021)
The discourse of traditional ecological knowledge and nature conservation in an eco-religious perspective is an essential issue to studie. This is because collective memory determines the relationship between environment, the Creator, humans, and the surrounding ecosystem. The purpose of this study is to explore the local wisdom of the Lamaholot ethnic that are still visible. The research method used qualitative approach with critical hermeneutic data presentation. Literature study is used to obtain data. The data were analyzed using the Gadamerian hermeneutic approach. The resulst showed that most of the Lamaholot ethnic communities live from and in agricultural culture. When opening new land for the agricultral area, it is always preceded by the practice of special rites that support farming activities. The agricultural culture practiced by the Lamaholot ethnicity is not a type of exploitative culture but is a representation of symbiotic mutualism. More than, farming rituals, mythology, fables, totems, taboos and metaphors in the Lamaholot ethnic agrarian culture are part of a very rich plus genius religious ecological folklore.Diskursus mengenai pengetahuan tradisional dan konservasi alam dalam persepktif eco-religi menjadi isu yang menarik untuk diteliti. Sebab, ingatan kolektif itulah yang menentukan relasi antara alam, Sang Pencipta, manusia, dan ekosistem lingkungan di sekitarnya. Tujuan penelitian ini adalah menggali kearifan lokal etnis Lamaholot yang masih nampak. Metode penelitian menggunakan pendekatan kualitatif dengan pemaparan data secara hermeneutis kritis. Studi pustaka digunakan untuk memperoleh data. Analisis data menggunakan pendekatan hermeneutik Gadamerian. Hasil penelitian ini menunjukkan bahwa sebagian besar masyarakat etnis Lamaholot hidup dari dan dalam kultur agrikultural. Saat membuka lahan baru untuk area ladang, selalu didahului dengan praktik ritus-ritus khusus yang menunjang aktivitas berladang. Kultur agrikultural yang dipraktikkan oleh etnis Lamaholot bukanlah sebuah tipe kultur eksploitatif melainkan bercorak mutualisme simbiosis. Lebih dari itu, ritual-ritual perladangan, mitologi, fabel, totem, tabu-tabu dan metafora di dalam kultur agraris etnis Lamaholot merupakan bagian dari folklor ekologi religius yang sangat kaya plus genius.